Stem cell-derived extracellular vesicles: A novel and potential remedy for primary ovarian insufficiency - Geng, Zixiang; Guo, Hailing; Li, Yifei; Liu, Ying; Zhao, Yongfang (Frontiers in Cell and Developmental Biology, 2023)
Primary ovarian insufficiency (POI) is an essential cause of young female fertility loss. At present, there are many treatments for POI, but due to the complexity of the pathogenesis of POI, the efficacy still could not be satisfactory. Stem cell transplantation is a feasible intervention protocol for POI. However, its wide application in the clinic is limited by some defects such as tumorigenic and controversial ethical issues. Stem cell-derived extracellular vesicles (EVs) represent an important mode of intercellular communication attracting increasing interest. It is well documented that stem cell-derived EVs for POI with exciting therapeutic effects. Studies have found that stem cell-derived EVs could improve ovarian reserve, increase the growth of follicles, reduce follicle atresia, and restore hormone levels of FSH and E2. Its mechanisms include inhibiting ovarian granulosa cells (GCs) apoptosis, reactive oxygen species, and inflammatory response and promoting GCs proliferation and angiogenesis. Thus, stem cell-derived EVs are a promising and potential method for POI patients. However, stem cell-derived EVs still a long way from clinical translation. This review will provide an overview of the role and the mechanisms of stem cell-derived EVs in POI, and further elaborate on the current challenges. It may suggest new directions for future research.